Crossroad of infection and autoimmunity in acute liver failure: a case report - Akash Roy (Egyptian Liver Journal, 2021)
Abstract Background Acute liver failure (ALF) is a syndromic diagnosis, consisting of jaundice, coagulopathy, and any degree of encephalopathy in a patient without pre-existing liver disease within 26 weeks of the onset of symptoms. Autoimmune hepatitis has a wide range of presentations and can rarely present as ALF, which frequently tends to be autoantibody negative. Tropical infections like dengue, malaria, and leptospirosis, which present as mimickers of ALF, always remain a differential diagnosis of ALF and mandate an etiology specific management. In rare cases, such infections themselves act as a trigger for autoimmunity. We report a case of diagnostic crossroads of infection and autoimmunity, presenting as acute liver failure and describe the challenges in management. Case presentation A 25-year-old female presented with a syndromic diagnosis of acute liver failure with possibility of tropical illness-related ALF mimic on account of positive Leptospira serology. After initial improvement, there was a rebound worsening of liver functions which prompted a liver biopsy. Biopsy narrowed the differential to Leptospira-associated hepatitis and severe auto-immune hepatitis. Trial of low dose steroid was given which led to dramatic improvement. Conclusion Tropical infections can present as ALF mimics and can themselves act as triggers for autoimmunity. Distinguishing such cases from de-novo acute severe autoimmune hepatitis is difficult and requires therapeutic brinksmanship. An early trial of steroid is mandated but comes with its own challenges.